2013
DOI: 10.3389/fimmu.2013.00066
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Inhibitors CK59 and CID755673 Alter Primary Human NK Cell Effector Functions

Abstract: Natural killer (NK) cells are part of the innate immune response and play a crucial role in the defense against tumors and virus-infected cells. Their effector functions include the specific killing of target cells, as well as the modulation of other immune cells by cytokine release. Kinases constitute a relevant part in signaling, are prime targets in drug research and the protein kinase inhibitor Dasatinib is already used for immune-modulatory therapies. In this study, we tested the effects of the kinase inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Further experimentation is needed to clarify this point. Recent studies have shown that different PKC isoforms are acting upstream of PKD1 (Scheiter et al, 2013). For example, PKCδ is upstream of PKD1 in reactive oxygen species-mediated mitochondrial depolarization (Zhang et al, 2015), and PKCδ knockdown effectively attenuates PKD1 activation (Asaithambi et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Further experimentation is needed to clarify this point. Recent studies have shown that different PKC isoforms are acting upstream of PKD1 (Scheiter et al, 2013). For example, PKCδ is upstream of PKD1 in reactive oxygen species-mediated mitochondrial depolarization (Zhang et al, 2015), and PKCδ knockdown effectively attenuates PKD1 activation (Asaithambi et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…To verify our hypothesis, by using a specific inhibitor CID755673, we disrupted PKD activity and assessed the polar body extrusion as well as the meiotic procession. Previous study indicated that the treatment with 5 μM CID755673 resulted in significant inhibition of NK cells [22]. Additionally, the phosphorylation levels of PKD were completely blocked at 50 μM CID755673 treatment [23].…”
Section: Discussionmentioning
confidence: 99%
“…PKD has been extensively studied in multiple cancer relevant pathological processes. Our review will focus on the impact of PKD in pathways pertinent to several hallmarks of cancer, including enhanced growth, proliferative capacity [ 6 , 7 , 39 , 41 , 42 ], evasion of cell death [ 6 , 43 , 44 , 45 ], migration and invasion [ 41 , 42 ], angiogenesis [ 46 , 47 ], and immune modulation [ 6 , 48 , 49 , 50 ]. The role of each PKD isoforms in each of the pathological process will be reviewed and discussed (see a summary on the contributary roles of PKD isoforms in cancer in Table 1 ).…”
Section: Pkd In Pathological Processes and Human Diseasesmentioning
confidence: 99%